MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO - Indah Annisa (Departemen Matematika, 2018)
Understanding of mathematical concepts is one of the learning objectives and basic skills that must be develoved optimally. But in fact students’s understanding of mathematical concepts is not optimal, it is also found in class VIII of SMPN 4 Padang. One of factors that cause this learning is not centered on students. Efforts to improve students’s understanding of mathematical concepts is using cooperative learning model the power of two. Type of research is quasi experimental with static group design. Purpose of research is to know whether students’s understanding of mathematical concepts who use cooperative learning model the power of two is better than conventional learning is class VIII of SMPN 4 Padang. Result of research show that indicate that students’s understanding mathematical concepts who use cooperative learning model the power of two is better than conventional learning is class VIII of SMPN 4 Padang. Keyword – cooperative learning model the power of two, conventional learning, understanding of mathematical concepts, conventional learning.